This Penanaman Nilai Kesalehan Sosial di Lembaga Pendidikan Muhammadiyah melalui Lembaga Zakat Infaq dan Shadaqah Muhammadiyah (LAZISMU) - Ardi Kiswanto; Mhd. Lailan Arqam (Universitas Muhammadiyah Prof Dr Hamka, 2023)
This study aims to determine the role of philanthropic institutions/LAZISMU in Muhammadiyah educational institutions in instilling the value of social piety to students. This research uses a qualitative approach. The data analysis method uses an inductive inference model, meaning that from specific facts general conclusions are drawn. The results showed that what was done by LAZISMU, especially SMK Muhammadiyah Imogiri, in planning and implementing work programs still considered instilling the value of social piety for all school residents. This is shown by the programs that have been prepared, namely in the collection of the one day one coint movement, incidental infaq care when there are local and national disasters. As for then in providing understanding that fosters the value of social piety with a program to use funds, namely the Mentari Scholarship program. Scholarships are given priority to underprivileged / poor students, orphans or orphans. The second program is the Free Ambulance Service for patients / families of the poor which is intended for armana operations. The last program that can also then instill awareness of the value of social piety is Indonesia Siaga, the distribution of disaster donations to those affected by the disaster.